Senam Adaptif Sebagai Media Terapi Gerak Bagi Siswa Berkebutuhan Khusus di SKH Muara Sejahtera - Apriliani, Ria; Sulistianingsih, Annisa (Abdimas Mandalika, 2026)
Abstract:  This community service program aimed to develop and implement adaptive gymnastics as a movement therapy medium for students with special needs at SKH Muara Sejahtera, Pamulang. The background of this activity was the low participation of students with hearing and intellectual disabilities in physical activities, limited teacher competence in adapted physical education, and the absence of structured adaptive exercise programs. Adaptive gymnastics was selected because it can be modified according to individual abilities and functions as movement therapy to improve coordination, balance, muscle strength, and socio-emotional development. The implementation method involved collaboration among lecturers, students, teachers, and parents through training, mentoring, and routine adaptive gymnastics practice over a two-month period. Evaluation was conducted using pre-post motor skill assessments, observation, and interviews with teachers and parents. The results showed and increase in student participation from 40% to 75% , improved motivation and confidence, and better coordination in most students, although independence and concentration still required further improvement. Teachers also gained new competencies in applying adaptive physical education strategies. This program demonstrates that adaptive gymnastics in an effective and feasible intervention to enhance motor development and learning participation of students with special needs in special schools.Abstrak: Program pengabdian kepada masyarakat ini bertujuan mengembangkan dan mengimplementasikan senam adaptif sebagai media terapi gerak bagi siswa berkebutuhan khusus di SKH Muara Sejahtera, Pamulang. Latar belakang kegiatan ini adalah rendahnya partisipasi siswa tunarungu dan tunagrahita dalam aktivitas jasmani, keterbatasan kompetensi guru dalam pendidikan jasmani adaptif, serta belum tersedianya program senam adaptif yang terstruktur. Senam adaptif dipilih karena dapat dimodifikasi sesuai kemampuan individu dan berfungsi sebagai terapi gerak untuk meningkatkan koordinasi, keseimbangan, kekuatan otot, serta perkembangan sosial-emosional siswa. Metode pelaksaan melibarkan kolaborasi dosem, mahasiswa, guru, dan orang tua melalui kegiatan pelatihan, pendampingan, serta praktik senam adaptif secara rutin selama dua bulan. Evaluasi dilakukan menggunakan asesmen motorik pra dan pasca kegiatan, observasi, serta wawancara dengan guru dan orang tua. Hasil kegiatan menunjukkan peningkatkan partisipas siswa dari 40% menjadi 75%, meningkatnnya motivasi dan rasa percaya diri siswa, serta perbaikan koordinasi gerak, meskipun aspek kemandirian dan konsentrasi masih memerlukan pendampingan lanjutan. Guru juga mengalami peningkatan kompetensi dalam menerapkan pendidikan jasmani adaptif. Program ini membuktikan bahwa senam adaptif merupakan intervensi yang efektif dan aplikatif untuk meningkatkan perkembangan motorik dan partisipasi belajar siswa berkebutuhan khusus di sekolah khusus.